Application of Spectral Computed Tomography Single-energy Technique to Small Bowel Crohn’s Disease - Pengfei WU; Chuanbing WANG (CT Lilun yu yingyong yanjiu)
Objective: To investigate the application of a double-layer detector spectral computed tomography (CT) single-energy technology for intestinal wall enhancement in Crohn’s disease enterography. Methods: Data from 43 patients with Crohn’s disease who underwent enterography using spectral CT between January 2023 and July 2024 were retrospectively collected. The 40~140 keV single level and conventional mixed energy images were reconstructed, and the CT value, noise, signal to noise ratio (SNR), and contrast to noise ratio (CNR) of the 40~140 keV single level and conventional mixed energy images were objectively evaluated using one-way ANOVA. The image quality was evaluated subjectively using the five point method, and the results were analyzed using the rank sum test. Differences in imaging features of Crohn’s disease activity were determined using the paired \begin{document}$χ^2 $\end{document} test. Results: Significant differences were observed in the CT value, noise, SNR, and CNR between the single-level and mixed-energy image groups. With an increase in single-level energy, the CT value, noise, SNR, and CNR of all images decreased, and each index was the highest at 40 keV. Pair-to-group comparisons showed that the CT value, noise, SNR, and CNR of the 40 keV images were significantly different from those of the other groups. A significant difference was absent in the CT value, noise, SNR, or CNR between the 70 keV and mixed energy image groups. The subjective score of the 40 keV image group was significantly higher than that of the mixed-energy image group. A statistical difference was absent between the mixed energy and 40 keV single-level image groups in the assessment of active Crohn’s disease. Conclusion: The overall image quality score of 40 keV single level enterocardiography is higher than that of conventional mixed-energy images, and therefore can improve and optimize the diagnosis of small bowel Crohn’s disease and be popularized in clinical applications.